Continuous ACL graft, results. Issue 1 (31st January 2017) - Díaz, Jorge Luis; Vega, Marcelo; Matesevach, Ivan
Objectives: describe our technique using hamstring graft that respects the proximal continuity of Semitendinosus and uses the superior biological potential of the distal periosteum., preserving and stressing the ST reinforce the retropulsión and dynamic control of external rotation of the knee. Here the technique, results, difficulties and foundations. Methods: The sample of this research was composed of 229 cases operated between 01/03/97 and 01/03/13 in Arthroscopy Private Center., 166 male and 63 female, the postop follow-up was 86 months. Evaluated with IKDC, Lysholm, Hamstring EMG. Comparative histology study in rabbits. Results: IKDC and Lysholm score showed 93% of very good results. Conclusion: Dynamic ACL reconstruction achieves a static-dynamic stabilization of the knee. Grafts have a plus in their biological potential (proximal continuity - osteo-periosteal insertion of the tendons in the femoral tunnel). The hamstring maintains its functionality (EMG). 93% satisfactory results (IKDC, Lysholm). It is a valid surgical option in ACL injuries.